South Africa's energy conundrum: the potential limiting effects of departmentalism on policy decision-making - Fraser, Ashleigh Claire (Department of Political Studies, 2014)
This thesis examines the departmentalism dilemma which South Africa's energy sector is faced with today. Many stakeholders play a vital role in addressing the production, distribution and consumption issues of the energy sector. However, many of these stakeholders do not work in a joined-up cooperative manner. This leads to incoherent, uncoordinated and incomplete policy decision-making which cripples the policy cycle. Today the energy sector is faced with the dilemma of climate change and how this directly affects what energy resources should be used to meet the demand of energy needs. Different stakeholders have differing interests when it comes to what types of energy policies should be integrated into the energy sector. As it stands, coal amounts for almost 95% of the energy mix while nuclear, gas and renewable energy are included in the balance of the energy mix. Coal is a low grade, dirty energy that has a dire impact on the environment. As 11 coal-fired power stations operate across the country with the construction of 2 more over the next 5 years, the amount of carbon dioxide that is released into the atmosphere from the burning of coal is on the increase. It is in the best interest of all energy stakeholders to adapt their energy strategies to include climate change mitigation action plans and work in a coordinated and cooperative manner. The National Planning Commission has continued to stress the importance of Joined-up governance. By managing this policy strategy and information, a central government department can promote a coherent, ?joined-up government? policy approach within and across departments and spheres. This approach should surely encourage better horizontal and vertical coordination and cooperation between stakeholders in the energy sector. In reality, improved cooperation and coordination cannot be achieved due to the self-focused attitudes of stakeholders. It is evident that out of the many energy stakeholders, Eskom, the dominant incumbent monopoly has captured energy policy decision-making. The theory on regulatory capture is an important theory to discuss in this case as it highlights how the policy making space is altered by an information asymmetry and how this impacts on role players and their grasp of the complexity in this space. The Department of Energy's dependence on Eskom has led to the loss of information and control and an information asymmetry and reliance is developed. Departmentalism and regulatory capture thus mutually reinforce each other. The legacy of domination, control and resistance of Eskom has recently been challenged by NERSA who has pushed back on much of Eskom's requests, to ensure that the public interest is protected. However, this is adversely affecting joined-up governance as it is deepening departmentalist tendencies. The role of Eskom and its tentative relationship with NERSA and the Department of Energy enhances departmentalism characteristics and promotes incoherent policy decisions. In order to tackle problems such as global climate change and poverty, successfully, energy policymakers need to consider ways in which departmentalism and regulatory capture, resulting in poor, incoherent policies, might be overcome.